Novel insights into the multifaceted roles of m6A-modified LncRNAs in cancers: biological functions and therapeutic applications - Jinxin Tang; Jinhui Zhang; Yu Lu; Jieyu He; Hua Wang; Binfeng Liu; Chao Tu; Zhihong Li (BMC, 2023)
Abstract N6-methyladenosine (m6A) is considered as the most common and important internal transcript modification in several diseases like type 2 diabetes, schizophrenia and especially cancer. As a main target of m6A methylation, long non-coding RNAs (lncRNAs) have been proved to regulate cellular processes at various levels, including epigenetic modification, transcriptional, post-transcriptional, translational and post-translational regulation. Recently, accumulating evidence suggests that m6A-modified lncRNAs greatly participate in the tumorigenesis of cancers. In this review, we systematically summarized the biogenesis of m6A-modified lncRNAs and the identified m6A-lncRNAs in a variety of cancers, as well as their potential diagnostic and therapeutic applications as biomarkers and therapeutic targets, hoping to shed light on the novel strategies for cancer treatment.